A simple strategy to achieve remarkable mechanochromism of cationic Ir(iii) phosphors through subtle ligand modification. Issue 43 (25th October 2018) - Zhao, Kai-Yue; Mao, Hui-Ting; Wen, Li-Li; Shan, Guo-Gang; Fu, Qiang; Sun, Hai-Zhu; Su, Zhong-Min
Abstract : Herein, a facile and feasible strategy to control the mechanochromism of Ir(iii ) complexes through simple adjustment of the dipole moment is reported. Abstract : A clear relationship between structures and desired properties is a crucial factor for further material design with diverse structure and performance optimization. Herein, a new design strategy to achieve efficient mechanochromism of Ir(iii ) complexes has been described by deeply exploring the photophysical properties of a series of cationic Ir(iii ) phosphors that contain the same main ligands but easily tunable donor–acceptor type ancillary ligands. All designed phosphors exhibit intense emissions in solid states due to intrinsic aggregation-induced emission (AIE) characteristics. By simply tuning the donor moieties on ancillary ligands, controllable and naked-eye visible mechanochromic luminescence behavior has been successfully realized. Compared with previous works, this design strategy reported herein is more simple and feasible. Subtle modification of the donor groups on ancillary ligands leads to obvious changes in the dipole moments. The larger the dipole moments, the more efficient is the mechanochromism for such a studied system. Benefiting from the prominent and reversible mechanochromism as well as intense emission in the aggregation state, an efficient data encryption device and a sensitive explosive probe towards 2, 4, 6-trinitrophenol (TNP) are achieved.